THE PRIVATIZATION OF THE MEANING AND ROLE OF PUBLIC SPACE IN THE CITY OF MALANG (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Public space is a container the activity of the community, which in general serves as a means of activity, the liaison between the space, barrier or distance between the space and softeners the formation of the architecture of the building. Ecologically functioning as a green open space, absorbing rain water, flood control, and maintenance of the ecosystem. Public space is characterized by three things: responsive, democratic and meaningful. One of the problems in big cities such as Malang is a frequent public space controlled, contested and commercialized by the parties and particular interests. This study aims to inventory and analyze the public spaces in the city of Malang that are privatized as a space of commodity economy and utility. The method used is field observation, and the results were analyzed by descriptive qualitative based on the theory of Carr. As a result, the path of pedestrians along the public space of the corridor Basuki Rahmat street, Jaksa Agung Suprapto, Parman, A. Yani, Kawi, road Corridor around the Large Market, and the City's main streets other unfortunates was taken over by the owner - managers of the buildings to the parking area of illegal cars and motorbikes, so pedestrians have a lot to maneuver among the vehicle park. As a result public space is extinct meaning and its role as a space of interaction democratic, and turned into the engineering space. The conditions of the anti-urban with the reason the pragmatism of the res economica has been to privatize public space. Attraction the reality of the urbanism already outnumbered by the space artificially and consumerism. The exoticism of the corridor Kayoetangan (Basuki Rahmat) as one of the historic landmarks of the pride of the citizens of the city of Malang as the great streets that are liveable has faded. The privatization of public space has made the citizens of the city of Malang at this time do not understand, understand, and appreciate the essence of public space.Key words: City, Malang, public, privatization, of space.